Women’s empowerment, food security and nutrition of pastoral communities in Tanzania - Galiè, Alessandra; Teufel, Nils; Girard, Amy W.; Baltenweck, Isabelle; Domínguez Salas, Paula; Price, Mindy J.; Jones, Rebecca; Lukuyu, Ben A.; Korir, Luke; Raskind, Ilana G.; Smith, Kristie; Yount, Kathryn M. (Elsevier, 2019)
This paper presents a mixed-methods study that examines the relationship between women’s empowerment, household food security, and maternal and child diet diversity (as one indicator of nutrition security) in two regions of Tanzania. Indicators across three domains of women’s empowerment were scored and matched to a household food insecurity access scale. Qualitative research helped appreciate the gender dynamics affecting the women’s empowerment-food security and women’s empowerment-nutrition security nexus. In cluster adjusted regression analyses, scores from each domain were significantly associated with women’s dietary diversity, but not with household food security. All three empowerment domains were positively associated with food security and nutrition in the qualitative analysis. This article discusses these findings and shows the pathways by which respondents saw their empowerment to affect their household food security.